“I Dreamed a Dream”: Linguistic Features and Characteristics of Dreams in the Hebrew Bible and Their Application in Contemporary Translations - Greed, Teija (The Bible translator, 2024)
Dreams play an important role in the Bible. They have been studied extensively from theological, hermeneutical, and cultural perspectives, but less attention has been given to more focused linguistic and discourse-analytic approaches. The key question of the current study is, How is “dream-ness” conveyed linguistically in the dreams of the Hebrew Bible? To this end, I explore four biblical dreams. Then, through four translations, I investigate how the biblical dream-ness has been transferred into these living languages. The frequent use of the discourse particle (wǝ)hinnēh together with the predicative “scenic” participle are identified as the key linguistic signals for biblical dream-ness. In the translations, a wide variety of linguistic choices are employed, including mirative and modal marking. This study shows that for a fuller appreciation of the functions of the elements in dream narratives, the researcher needs to go beyond linguistics to other domains, especially poetics.